How the rate of change and control of a modular product architecture impact firm‐level outcomes. (7th January 2020) - Galvin, Peter; Burton, Nicholas; Bach, Norbert; Rice, John
Abstract: Who controls a product architecture and the rate at which this architecture changes, impacts the type of outcomes a firm can expect to derive from utilizing a modular product architecture? Advantages such as increased levels of innovation, quick determination of consumer preferences and lower production costs have been linked to modular product architectures. However, such architectures have also been linked to detrimental outcomes such as high levels of competition and commoditization along with higher development costs. It is via the introduction of two key moderating variables that we improve our understanding of the impact that a modular product architecture has upon different firm‐level outcomes.